Ribosomal protein S6 promotes stem‐like characters in glioma cells - Shirakawa, Yuki (Cancer Sci, 2020)
Glioblastoma multiforme (GBM), a lethal brain tumor developing in the white matter of the adult brain, contains a small population of GBM stem cells (GSCs), which potentially cause chemotherapeutic resistance and tumor recurrence. However, the mechanisms underlying the pathogenesis and maintenance of GSCs remain largely unknown. A recent study reported that incorporation of ribosomes and ribosomal proteins into somatic cells promoted lineage trans‐differentiation toward multipotency. This study aimed to investigate the mechanism underlying stemness acquisition in GBM cells by focusing on 40S ribosomal protein S6 (RPS6). RPS6 was significantly upregulated in high‐grade glioma and localized at perivascular, perinecrotic, and border niches in GBM tissues. siRNA‐mediated RPS6 knock‐down significantly suppressed the characteristics of GSCs, including their tumorsphere potential and GSC marker expression; STAT3 was downregulated in GBM cells. RPS6 overexpression enhanced the tumorsphere potential of GSCs and these effects were attenuated by STAT3 inhibitor (AG490). Moreover, RPS6 expression was significantly correlated with SOX2 expression in different glioma grades. Immunohistochemistry data herein indicated that RPS6 was predominant in GSC niches, concurrent with the data from IVY GAP databases. Furthermore, RPS6 and other ribosomal proteins were upregulated in GSC‐predominant areas in this database. The present results indicate that, in GSC niches, ribosomal proteins play crucial roles in the development and maintenance of GSCs and are clinically associated with chemoradioresistance and GBM recurrence.